2013
DOI: 10.1136/neurintsurg-2013-010941
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy of cyclic vs static aspiration in a cerebral thrombectomy model: an initial proof of concept study

Abstract: Cyclic aspiration significantly outperformed static aspiration in speed and overall clearance of synthetic clots in our experimental model. Within cyclic aspiration, efficacy is improved by increasing cycle frequency, utilizing specific pressure cycle waveforms and using water rather than air as the aspiration medium. These findings provide a starting point for altering existing thrombectomy technology or perhaps the development of new technologies with higher recanalization rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…In addition to the aspiration force, the use of cyclical aspiration instead of continuous aspiration could result in higher first-pass recanalization rates and lower distal clot embolization. 31 32 One hypothesis is that cyclical aspiration allows larger clot ingestion into the aspiration catheter and causes less clot fragmentation than continuous aspiration. 31 Although DA could be used with either a long introducer sheath or a BGC, recent retrospective studies have shown that utilization of a BGC might improve the final and first-pass recanalization rates.…”
Section: Factors Influencing the Success Of Direct Aspiration Technicmentioning
confidence: 99%
“…In addition to the aspiration force, the use of cyclical aspiration instead of continuous aspiration could result in higher first-pass recanalization rates and lower distal clot embolization. 31 32 One hypothesis is that cyclical aspiration allows larger clot ingestion into the aspiration catheter and causes less clot fragmentation than continuous aspiration. 31 Although DA could be used with either a long introducer sheath or a BGC, recent retrospective studies have shown that utilization of a BGC might improve the final and first-pass recanalization rates.…”
Section: Factors Influencing the Success Of Direct Aspiration Technicmentioning
confidence: 99%
“…Our results showed that overall labeled-ID correlated with the achieved experimental asp-F, however, we observed that larger catheters did not necessarily lead to the highest asp-F, or catheters with identical labeled-ID showed up to 13.05 % variability in their experimental asp-F. Our findings, in line with previous publications [10], confirm that labeled-ID is not the only factor determining the experimental asp-F of a device and therefore, additional variables should be considered. Long et al [16] presented a novel catheter design and demonstrated that a larger proximal ID could [17] also increase the eff-ID of the catheter and consequently, the asp-F. Boisseau et al [12] re-ported in their review that, besides catheter labeled-ID, other factors like the use of cyclical aspiration [18], [19] or balloon guide catheter [17], the contact angle between clot and catheter [20] and the clot composition [21] may influence the success of aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on cyclical aspiration, a SOFIA Plus catheter (MicroVention Inc., Aliso Viejo, CA) had static (29 inHg) or cyclical (18–29 inHg, 0.5 Hz) aspiration employed using the digital CLEAR Aspiration System (Insera Therapeutics, Sacramento, CA) and eight thrombus aspiration experiments were conducted for each aspiration type in a flow model. The study showed that by varying the pressure dynamics through cyclical aspiration, it increased aspiration force on the occlusion as well as resulted in more successful clot clearance when compared with static aspiration ( 48 ). The cause of this improved ingestion may be due to the initial clot softening from dynamic compression or that dynamic friction is less than the static friction that occurs when the thrombus is stuck at the tip of the catheter.…”
Section: Devicesmentioning
confidence: 99%